The Effect of A Training Program (Physical – Skill) On The Development Of Alactic Capacity In Young Volleyball Players - Saleh, Rafea; Sobhan, Hussein (Journal of Physical Education, 2008)
The researchers conducted this study to indicate that evaluation and measurement in identifying the capacities and levels of development whether physical, skill, or physiological still need more attention. Most measurement tools witnessed great development like the methods of training. The study aimed at identifying the effect of the training program on physical abilities as well as alactic and skill abilities. The subjects were young volleyball players of the age 19 years old. The researchers used the experimental method. They also used scientific tools for measurement. They concluded that the players' physical and skill abilities affect their level of alactic capacity .The researchers recommended selecting sport specific physical abilities that suits their age to develop the muscle to be able to resist fatigue and maintain the level of achievement